Respuesta :
Answer:
(x - 3)(5x - 3)
Step-by-step explanation:
Assuming you require the expression to be factorised.
Given
5x² - 18x + 9
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 5 × 9 = 45 and sum = - 18
The factors are - 15 and - 3
Use these factors to split the x- term
5x² - 15x - 3x + 9 ( factor the first/second and third/fourth terms )
= 5x(x - 3) - 3(x - 3) ← factor out (x - 3) from each term
= (x - 3)(5x - 3) ← in factored form
Answer: (5x-3)(x-3) For Factorization and x=3/5, 3 for Quadratic Equation.
Step-by-step explanation:
Factorization
[tex]5x^2-18x+9[/tex]
Two numbers multiply to 5 are 5 and 1
Two numbers multiply to 9 are (1 and 9) and (3 and 3)
[tex](5x-3)(x-3)[/tex] You can try use 1 and 9 but it's wrong so I'm skipping it.
(5x)(x) = 5x^2 Correct
[(5x)(-3)]+[(-3)(x)] = -15x-3x = -18x Correct
(-3)(-3) = 9 Correct
The answer for Factorization is (5x-3)(x-3)
Quadratic Equation
Just same, Factoring and you get [tex](5x-3)(x-3)=0[/tex] then find the value of x
[tex]x=\frac{3}{5}, 3[/tex] for the answer.